The Relationship Between Prior Knowledge and Students’ Chemical Literacy - Pebriani, Nur Indah; Aini, Faizah Qurrata (Jurnal Pijar Mipa, 2025)
Chemical literacy is a key component of scientific literacy, enabling individuals to understand, evaluate, and apply chemical concepts in real-life situations. This study investigates the relationship between students' prior knowledge and their chemical literacy on acid-base topics in senior high school. The study employed a quantitative descriptive method with a correlational approach, involving 99 eleventh-grade students from three accredited private schools in Padang City, Indonesia. Two validated instruments were used to collect data: the Structured Essay Diagnostic Test of Chemistry (SEDToC) to assess prior knowledge, and a discourse-based chemical literacy test. Data analysis included descriptive statistics and Spearman's Rank correlation. Results revealed a very weak and statistically insignificant positive correlation between prior knowledge and chemical literacy (rₛ = 0.1454; p > 0.05), with a coefficient of determination (r²) of 2.1%. Stoichiometry emerged as the subtopic with the highest level of understanding (41.68%), while chemical bonding was the lowest (3.05%). Although most students demonstrated procedural understanding, many struggled with contextual and discourse-based questions that required higher-order thinking. A high rate of misconceptions (36.59%) was also identified, which negatively affected students’ ability to reason and interpret chemical phenomena accurately. This study highlights that conceptual understanding alone is insufficient to support chemical literacy. The novelty of this research lies in its focus on chemical literacy as a multidimensional construct, beyond mere content mastery. The findings suggest that instructional strategies should not only strengthen prior knowledge but also integrate real-world contexts and promote critical thinking. Future research is recommended to explore other contributing factors such as motivation, metacognitive awareness, and teaching approaches that could better foster students’ chemical literacy. To support this, educators should design learning strategies that go beyond reinforcing prior knowledge and emphasise contextual, inquiry-based, and reflective approaches to develop students' comprehensive chemical literacy.